Intracorneal blood removal six weeks after canaloplasty - Alberto Rossetti; Norbert Koerber; Daniele Doro (Indian Journal of Ophthalmology, 2013)
In a 71-year-old patient with bilateral open-angle glaucoma, intracorneal blood was found after a canaloplasty procedure in the right eye. Six weeks after surgery on ultrasound biomicroscopy examination, liquified blood and blood clots could be observed nasally in the deep corneal stroma close to the Descemet′s membrane. The intracorneal blood was washed out with balanced saline solution following deep corneal incision and lamellar dissection. Descemet′s membrane was reattached with air injection into the anterior chamber. Two months later, visual acuity improved to 20/50, intraocular pressure was 16 mm Hg without medication and confocal microscopy showed deep stromal folds and limited endothelial cell loss. Viscoelastic entering the cornea at Schwalbe′s line and reflux of blood from the collector channels to Schlemm′s canal can account for corneal hematoma. Even six weeks after canaloplasty, successful blood removal could be fulfilled without rupturing the Descemet′s membrane.